Melting temperature control in coextruding process - Леваничев, Виталий Валерьевич (Eastern-European Journal of Enterprise Technologies, 2013)
Modern co-extrusion manufacturing of flexible multilayer polymeric packaging materials is considered as multiproduct and, in some cases, limited. Most readjustments require the change of feedstock composition. This affects the temperature profile of extruder, backpressure and requires prompt adjustment of technological modes. The influence of technological parameters on the melting temperature in co-extrusion processes was studied. Investigations were carried out on 18 extruders, installed on 4 co-extrusion units with screw diameters from 25mm to 50mm, observations lasted for 1 month. It is shown that the relative error of forecasting the melting temperature by mean temperature value in zones of extruder is ±12, 8% for the interval of ±2S. For more comprehensive analysis of heat exchange in extruder and the process control it was proposed to use the parameter - the percentage of heaters activation, which is standard for modern microprocessor temperature controllers.